Learning Natural Programs from a Few Examples in Real-Time - Natarajan, Nagarajan; Simmons, Danny; Datha, Naren; Jain, Prateek; Gulwani, Sumit (AIStats, 2019)
Programming by examples (PBE) is a rapidly growing subfield of AI, that aims to synthesize user-intended programs using input-output examples from the task. As users can provide only a few I/O examples, capturing user-intent accurately and ranking user-intended programs over other programs is challenging even in the simplest of the domains. Commercially deployed PBE systems often require years of engineering effort and domain expertise to devise ranking heuristics for real-time synthesis of accurate programs. But such heuristics may not cater to new domains, or even to a different segment of users from the same domain. In this work, we develop a novel, real-time, ML-based program ranking algorithm that enables synthesis of natural, user-intended, personalized programs. We make two key technical contributions: 1) a new technique to embed programs in a vector space making them amenable to ML-formulations, 2) a novel formulation that interleaves program search with ranking, enabling real-time synthesis of accurate user-intended programs. We implement our solution in the state-of-the-art PROSE framework. The proposed approach learns the intended program with just one I/O example in a variety of real-world string/date/number manipulation tasks, and outperforms state-of-the-art neural synthesis methods along multiple metrics.